Microbiological quality of freshwater prawns during storage - Abu Bakar, Fatimah; Salleh, Abu Bakar; Abdul Razak, Che Nyonya; Basri, Mahiran; Ching, Mai Keow; Radu, Son (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2008)
Microbiological quality analysis of freshwater prawns from three sampling sites in Peninsular Malaysia viz: Site 1- Kg. Jumbang, Negri Sembilan; Site 2- Kg. Cangkat Tin, Perak and Site 3- Kg. Cenderiang, Perak for total mesophilic and psychrophilic aerobic counts, proteolytic bacterial counts, histamine producing bacteria, cadaverine producing bacteria and putrescine producing bacteria in the prawns and pond water for the three sites showed that the microbiological quality of freshwater prawns is related to the microflora of pond water in which they were grown. The initial bacterial counts indicated the values were in the range of log 4+ CFU/g for all samples. Total mesophilic and psychrophilic counts of the head regions were higher than that of the body regions for all prawn samples and types of growth media tested. All samples showed an increase in counts with time and temperature of storage up to log 7+ CFU/g for mesophilic counts after 12 hours at ambient, 6 days at 10 ± 2°C and 12 days at iced storage. The samples from Site 2 had relatively higher counts compared to the other two sites which correlated well with the levels determined in the pond water. Similar trends were observed for psychrophilic counts but at lower values for the different types of media studied. Effects of preservatives on quality changes and shelf life of shrimp during iced storage indicated that boric acid, lactic acid and sodium metabisulphite managed to inhibit psychrophilic bacteria and biogenic amines formation in prawns while maintaining the mesophilic counts at lower levels during iced storage.